Pengembangan Media Diosidro (Diorama Siklus Hidrologi) pada Mata Pelajaran IPA Kelas V SDN 272 Wadeng - Shinta Kusniawati; Nataria Wahyuning Subayani (Journal on Education, 2023)
This study aims to develop diosidro learning media by identifying the feasibility of learning media through validity, responsiveness, and effectiveness. This research is research and development, through the ADDIE model which consists of analysis, design, development, implementation, evaluation. The analysis stage is carried out by identifying the needs for developing hydrological cycle diorama media through interviews and observations. The design stage by designing the framework and diosidro prototype. The develop stage is by compiling diosodro media according to the design and validating the media to 2 experts, namely material experts and media experts. The validation results of the material expert 1 obtained a score of 93.3%, the material expert 2 obtained a score of 85%, the media expert 1 obtained a score of 90%, and the validation of the media expert 2 obtained a score of 95% with a very valid category. The media is implemented in one class of 25 students with a learning achievement test obtaining a score of 84% in the complete category. And the results of the student response questionnaire obtained a score of 86.5% in the very good category. Diosidro media can be said to be feasible after media validation and can be said to be effective after conducting trials.